ANALISIS KEPASTIAN HUKUM PENJAMIN PERORANGAN YANG MELEPASKAN HAK ISTIMEWA DAN DIMOHONKAN DALAM PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG (PKPU) (STUDI PUTUSAN: Nomor 141/Pdt.Sus-PKPU/2020/PN.Niaga Jkt.Pst) - Reny Agustini; ariawan ariawan (Jurnal Hukum Adigama, 2021)
In this era of globalization more and more people are plunging into the field of business. In his decision to dive into the field of business, not a few people are willing to borrow credit for the sake of business continuity. In the case of this Lender the Bank must receive a guarantee first to guarantee the repayment of the debt. The current guarantee is not enough just in the form of material guarantees but often requested third-party guarantees. In this case, it is a Personal Guarantee. In the event of a Guarantee, the Creditor will ask the Guarantor to waive its privileges in a special agreement between the Creditor and the Guarantor. This resulted in his position. If many debtors do not pay their debts, lancer will request Postponement in debt repayment obligations. But nowadays not only debtors are requested but guarantors are also requested. This is a very dilemma and until now there is no Legal Certainty on the matter of guarantors requested for Postponement in debt repayment obligations. This is due to the difference in the interpretation of the waiver of privileges and the existence of special provisions in the Bankruptcy Law and Postponement in debt repayment obligations that do not govern clearly and specifically. So this matter becomes uncertain.